Effect of Intraoperative Goal-directed Balanced Crystalloid versus Colloid Administration on Major Postoperative Morbidity: A Randomized Trial. (May 2019) - Kabon, Barbara; Sessler, Daniel I.; Kurz, Andrea; Maheshwari, Kamal; Babazade, Rovnat; Fiffick, Alexa; Gazmuri, Ignacia; Ghobrial, Michael; Honar, Hooman; Kot, Michael; Kopyeva, Tatyana; Koyuncu, Onur; et al.
Editor's Perspective: What We Already Know about This Topic: Crystalloid solutions leave the circulation quickly, whereas colloids remain for hours, thus promoting hemodynamic stability. However, colloids are expensive and promote renal toxicity in critical care patients. Whether goal-directed intraoperative tetrastarch colloid administration reduces complications or promotes renal injury remains unknown. What This Article Tells Us That Is New: In a large randomized trial comparing intraoperative goal-directed 6% hydroxyethyl starch with goal-directed lactated Ringer's solution in patients having major abdominal surgery, 6% hydroxyethyl starch reduced neither a composite of serious complications nor the duration of hospitalization. However, 6% hydroxyethyl starch did not cause acute or long-term renal toxicity. Background: Crystalloid solutions leave the circulation quickly, whereas colloids remain for hours, thus promoting hemodynamic stability. However, colloids are expensive and promote renal toxicity in critical care patients. This study tested the hypothesis that goal-directed colloid administration during elective abdominal surgery decreases 30-day major complications more than goal-directed crystalloid administration. Methods: In this parallel-arm double-blinded multicenter randomized trial, adults having moderate- to high-risk open and laparoscopically assisted abdominal surgery with general anesthesia were randomly assigned to Doppler-guided intraoperative volume replacement with 6% hydroxyethyl starch 130/0.4 (n = 523) or lactated Ringer's solution (n = 534). The primary outcome was a composite of serious postoperative cardiac, pulmonary, infectious, gastrointestinal, renal, and coagulation complications that were assessed with a generalized estimating equation multivariate model. The primary safety outcome was a change in serum creatinine concentration up to 6 months postoperatively, compared to baseline concentrations. Results: A total of 1, 057 patients were included in the analysis. Patients assigned to crystalloid received a median [quartile 1, quartile 3] amount of 3.2 l [2.3, 4.4] of crystalloid, and patients assigned to colloid received 1.0 l [0.5, 1.5] of colloid and 1.8 l [1.2, 2.4] of crystalloid. The estimated intention-to-treat common effect relative risk for the primary composite was 0.90 for colloids versus crystalloids (95% CI: 0.65 to 1.23, P = 0.51), and 18% (91 of 523) of colloid patients and 20% (103 of 534) of crystalloid patients incurred at least one component of the primary outcome composite. There was no evidence of renal toxicity at any time. Conclusions: Doppler-guided intraoperative hydroxyethyl starch administration did not significantly reduce a composite of serious complications. However, there was also no indication of renal or other toxicity. Abstract : In a large randomized trial comparing intraoperative goal-directed 6% hydroxyethyl starch with goal-directed lactated Ringer's solution in patients having major abdominal surgery, 6% hydroxyethyl starch reduced neither a composite of serious complications nor the duration of hospitalization. However, 6% hydroxyethyl starch did not cause acute or long-term renal toxicity.